PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN BUDIDAYA AYAM PETELUR DI SMK N 2 CILAKU - ISABELA, ISABELA (2012)
Fun learningcan increasestudents'interestin learningandmeaningfulness. JigsawCooperative LearningModelis alearningstylethat encouragesactive studentgroupsand help each othertomaster the subject matteras well asto fostera sense of responsibilityin thediscussion.Student learning outcomesarelower thansubjectsRaisingChickensLayinga problemonLayerRaisinglearning. This phenomenonhappenseveryyear, especially in SMKNegeri 2Cilakuisthe percentageof students whoscoredaboveKKMverylow. The main objectiveof this studywas to determineimprovedlearning outcomesanddeterminetheincrease in activityclassXIstudentATU(Agribusiness poultry) after application ofTypesJigsawCooperative LearningModel. This study was conductedatSMKN 2CilakuCianjurfor threecycles of learning. The subjects werestudents of classXI, amounting to 10 people. The research methodused wasaction research. The instrumentsused areobservation sheetsandtests. UsingCooperative LearningJigsawstylecan enhancelearning activitiesand student learning outcomesin subjectsATUXIRaisingChickensLayinginSMKNegeri 2Cilaku. Improvedlearning outcomesindicated by theincrease in value ofNGainfrom cycle to cyclewiththe average value ofNGainonthe third cycleof0.69333and into thecategory ofpretty.